Efektifitas Metode Role-play dalam Meningkatkan Kemampuan Berbicara Bahasa Jepang pada Calon Pekerja Migran Indonesia di Balai Latihan Kerja - Amalia, Aan; Sundasewu, Rama Ulun; Ranadireksa, Dinda Gayatri (Japanology: The Journal of Japanese Studies, 2023)
The business relationship between Indonesia and Japan continues to strengthen in line with the increasing number of Indonesian migrant workers in Japan. As of June 2023, there were 25,337 Indonesian Migrant Workers (PMI) working in Japan through the Specified Skilled Worker (SSW) program, and the number of Indonesian apprentices reached 45,919 as of December 2022. These workers are required to have Japanese language skills. This study aims to determine the effectiveness and relevance of one method in Japanese language learning, namely the role-play method, in improving Japanese speaking skills among prospective PMI. The research method involved distributing questionnaires to 17 prospective PMI undergoing training at a vocational training center (BLK). The results revealed that the majority of respondents experienced increased confidence after participating in Japanese language learning through the role-play method. The main challenges faced were generally related to vocabulary and sentence structure; however, the role-play method was found to be highly engaging and helpful in improving speaking skills. Japanese language learning requires an interactive approach to build confidence and effective understanding, and in this case, role-play has proven to be an effective method in enhancing interest, engagement, and Japanese speaking ability.